Rancang bangun sistem monitoring suhu 10 channels berbasis mikrokontroler - Rustam Efendi; Arjal Tando; La Ode Sabara; Irwansyah Irwansyah (BKS-TM Indonesia, 2025)
A temperature monitoring system is essential in research, especially in the field of energy conversion in the Mechanical Engineering Study Program. One of the most commonly used systems is a data logger; however, its high cost often limits accessibility. An alternative hardware that can function as a data logger is the Arduino microcontroller. This study aims to design and develop a 10-channel temperature data logger system based on a microcontroller using the CJMCU MAX31856 amplifier module. The system integrates a type-K thermocouple sensor, DS3231 RTC module, SD Card module, and OLED display. The research applies both hardware and software design methods, covering component selection, hardware assembly, programming, and functional testing with calibration. The system was tested in a laboratory for three days to monitor the room temperature. The results showed that data from all channels overlapped closely, although minor measurement errors occasionally occurred. Linear regression analysis yielded an R² of 0.99, indicating high accuracy compared with an Autonic temperature controller. Further testing on copper pipes exposed to hot-water heat transfer showed a temperature increase trend, with readings ranging from 27 °C to 39 °C. The system proves reliable, accurate, and cost-efficient for laboratory energy research applications.